Comparative distribution of Arcadlin/Protocadherin‐8 mRNA in the intact and ischemic brains of adult mice. Issue 11 (3rd April 2022) - Inoue, Yosuke; Sawano, Toshinori; Yamaguchi, Natsumi; Inoue, Shota; Takayama, Akinori; Nakazawa, Shuma; Inagaki, Shinobu; Nakatani, Jin; Tanaka, Hidekazu
Abstract: The structural plasticity of dendritic spines serves as the adaptive capabilities of the central nervous system to various stimuli. Among these stimuli, cerebral ischemia induces dynamic alterations in neuronal network activity. Arcadlin/Paraxial protocadherin/Protocadherin‐8 (Acad), a regulator of dendritic spine density, is strongly induced by activating stimuli to the neurons. However, the detailed distribution of Acad in normal and ischemic adult brains remains unclear. We comprehensively described Acad expression patterns in normal and ischemic adult brains by in situ hybridization histochemistry. We found that intact adult brains expressed Acad in the piriform cortex, dentate gyrus, hippocampal CA3, entorhinal cortex, amygdala, and hypothalamus. Acad expression was dramatically upregulated in the piriform cortex, olfactory area, dentate gyrus, entorhinal cortex, prefrontal cortex, insular cortex, amygdala, and septohippocampal nucleus 4 h after cerebral ischemia. Cerebral ischemia induced widespread neuronal activation, which was required for Acad upregulation. Our data suggested the involvement of Acad in the adaptive plasticity and remodeling of the neuronal network in the limbic and paralimbic systems. Abstract : Arcadlin/Paraxial protocadherin/Protocadherin‐8 (Acad) is a regulator of dendritic spine density. We comprehensively described Acad expression patterns in normal and ischemic adult brains by in situ hybridization histochemistry. Acad was substantially expressed in the piriform cortex, hippocampus, entorhinal cortex, amygdala, and hypothalamus of intact brains. Cerebral ischemia dramatically upregulated Acad expression, mainly in the limbic and paralimbic regions. The upregulation of Acad depended on neuronal activation following cerebral ischemia. Our data provide insight into the mechanisms underlying neuronal plasticity after brain ischemia.